An Effective Green Porous Structural Adhesive for Thermal Insulating, Flame-Retardant, and Smoke-Suppressant Expandable Polystyrene Foam. (October 2022) - Li, Meng-En; Zhao, Hai-Bo; Cheng, Jin-Bo; Wang, Ting; Fu, Teng; Zhang, Ai-Ning; Wang, Yu-Zhong
Abstract: To develop an efficient way to overcome the contradiction among flame retardancy, smoke suppression, and thermal insulation in expanded polystyrene (EPS) foams, which are widely used insulation materials in buildings, a novel "green" porous bio-based flame-retardant starch (FRS) coating was designed from starch modified with phytic acid (PA) that simultaneously acts as both a flame retardant and an adhesive. This porous FRS coating has open pores, which, in combination with the closed cells formed by EPS beads, create a hierarchically porous structure in FRS–EPS that results in superior thermal insulation with a lower thermal conductivity of 27.0 mW·(m·K) − 1 . The resultant FRS–EPS foam showed extremely low heat-release rates and smoke-production release, indicating excellent fire retardancy and smoke suppression. The specific optical density was as low as 121, which was 80.6% lower than that of neat EPS, at 624. The FRS–EPS also exhibited self-extinguishing behavior in vertical burning tests and had a high limiting oxygen index (LOI) value of 35.5%. More interestingly, after being burnt with an alcohol lamp for 30 min, the top side temperature of the FRS–EPS remained at only 140 °C with ignition, thereby exhibiting excellent fire resistance. Mechanism analysis confirmed the intumescent action of FRS, which forms a compact phosphorus-rich hybrid barrier, and the phosphorus-containing compounds that formed in the gas phase contributed to the excellent flame retardancy and smoke suppression of FRS–EPS. This novel porous biomass-based FRS system provides a promising strategy for fabricating polymer foams with excellent flame retardancy, smoke suppression, and thermal insulation.